PEMANFAATAN TANAMAN OBAT SEBAGAI OBAT TRADISIONAL OLEH MASYARAKAT DESA TAMPAR AMPAR KECAMATAN PUJUT KABUPATEN LOMBOK TENGAH - Saputri, Audia; Rahmawati, Sri; Hardani, Hardani; Idawati, Sri (Pharmaceutical and Traditional Medicine, 2023)
This paper aims to determine the use of medicinal plants in the community and to determine the types of medicinal plants used by the people of tampar ampar village pujut district. Local know ledge about medicinal plants is obtained based on experience passed down from generation to generation. This study uses a qualitative descriptive method with data collection techniques through interviews, observation, and documentation. The results showed that most of the people in the vallage of Tampar Ampar still use medicinal plants as ingredients to treat diseases. Many medicinal plants grow wild around their neighborhood, and some are planted around the house. Treatment with plant ingredients is usually done by people who know very well about medicinal plants. The use of medicinal herbs to cure various diseases, namely aconomic factors, limited medical personnel, personnel and social. Medicinal plants are considered safe and have less side effects, lacuk af knowledge about medical treatment and easy service time.